Equivalent Cardioprotection Induced by Ischemic and Hypoxic Preconditioning - Xiang, Xujin; Lin, Haixia; Liu, Jin; Duan, Zeyan (The Thoracic and Cardiovascular Surgeon, 2013)
Objective We aimed to compare cardioprotection induced by various hypoxic preconditioning (HPC) and ischemic preconditioning (IPC) protocols.Methods Isolated rat hearts were randomly divided into 7 groups (n = 7 per group) and received 3 or 5 cycles of 3-minute ischemia or hypoxia followed by 3-minute reperfusion (IPC33 or HPC33 or IPC53 or HPC53 group), 3 cycles of 5-minute ischemia or hypoxia followed by 5-minute reperfusion (IPC35 group or HPC35 group), or 30-minute perfusion (ischemic/reperfusion group), respectively. Then all the hearts were subjected to 50-minute ischemia and 120-minute reperfusion. Cardiac function, infarct size, and coronary flow rate (CFR) were evaluated.Results Recovery of cardiac function and CFR in IPC35, HPC35, and HPC53 groups was significantly improved as compared with I/R group (p < 0.01). There were no significant differences in cardiac function parameters between IPC35 and HPC35 groups. Consistently, infarct size was significantly reduced in IPC35, HPC35, and HPC53 groups compared with ischemic/reperfusion group.Conclusion Multiple-cycle short duration HPC exerted cardioprotection, which was as powerful as that of IPC.
Keywords: ischemic preconditioning; hypoxic preconditioning; reperfusion injury